The use of emergency contraception among female senior high students in the Ho municipality of the Volta Region, Ghana - Konlan, Kennedy D.; Amoah, Roberta M.; Saah, Joel A.; Doat, Abdul Razak; Konlan, Kennedy Dodam; Japiong, Milipaak; Abdulai, Juliana A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Emergency contraception (EC) is one option for preventing unplanned pregnancy when it is available and properly used. Unsafe abortions are responsible for nearly one third of maternal deaths in sub-Saharan Africa and about quarter of unsafe abortions are among teenagers. Methods: A quantitative descriptive cross-sectional study. Data was collected using a pretested questionnaire. 260 senior high students were selected using a systematic sampling method in the Volta Region, Ghana. Data were cleaned and entered into SPSS version 22 and analysed into descriptive statistics. Results: Respondents acquired awareness about EC from friends (36.9%), family members (5.6%) and the mass media (41.6%). The required time for EC to be taken were stated as immediately after sex (57.9%), 24 hours after sex (1.2%) and (30.6%) did not know. 28.4% of participants indicated they would not use EC in the future as their faith was against it, 18.0% believed EC is ineffective and 24.9% consider it dangerous to their health. Reasons for use of EC included condom slipped (35.7%), inability to be on daily pill (33.7%), forced unprotected sex (8.2%) and miscalculation of the safe menstrual period (22.4%). There was a significant relationship between age and history of use of EC (p=0.000, c2=8.128, n=260). Conclusions: Strengthening education in Senior High Schools on sexual and reproductive health, with special emphasis on emergency contraceptives as a pregnancy preventive procedure will remain imperative to reducing the canker of maternal mortality attributed to adolescent abortions while improving understanding of the appropriate use of EC.